2017
DOI: 10.1200/jco.2016.67.2642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extent of Resection on Local Control and Survival in Patients From the COG A3973 Study With High-Risk Neuroblastoma

Abstract: This analysis of patients in the Children's Oncology Group A3973 study evaluated the impact of extent of primary tumor resection on local progression and survival and assessed concordance between clinical and central imaging review-based assessments of resection extent. Patients and MethodsThe analytic cohort (n = 220) included patients who had both central surgery review and resection of the primary tumor site. For this analysis, resection categories of , 90% and $ 90% were used, with data on resection extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 24 publications
4
99
2
Order By: Relevance
“…The 5-year overall survival (OS) rate of 2266 patients with recurrence was only 20% ± 1%, and patients who relapsed between 6 and 18 months after diagnosis had the highest risk of death (the peak value was at approximately 12 months), which also supports the results of our study [21]. According to previous clinical studies, the most common recurrence sites in high-risk NB patients are bone and bone marrow, while the 5-year local recurrence rate of the primary site is only 11.9% ± 2.2% [22]. In this study, among 14 patients with disease progression or recurrence, 13 experienced intraperitoneal progression or recurrence; these patients often presented with diffuse intraperitoneal lesions, which strongly suggested that progression and recurrence were related to implant metastasis caused by tumor rupture.…”
Section: Discussionsupporting
confidence: 90%
“…The 5-year overall survival (OS) rate of 2266 patients with recurrence was only 20% ± 1%, and patients who relapsed between 6 and 18 months after diagnosis had the highest risk of death (the peak value was at approximately 12 months), which also supports the results of our study [21]. According to previous clinical studies, the most common recurrence sites in high-risk NB patients are bone and bone marrow, while the 5-year local recurrence rate of the primary site is only 11.9% ± 2.2% [22]. In this study, among 14 patients with disease progression or recurrence, 13 experienced intraperitoneal progression or recurrence; these patients often presented with diffuse intraperitoneal lesions, which strongly suggested that progression and recurrence were related to implant metastasis caused by tumor rupture.…”
Section: Discussionsupporting
confidence: 90%
“…Incomplete resection is often the only choice to avoid serious or even lifecompromising complications. In contrast, with the LNESG1 study that included stage 1 and 2 localized resectable NBs without MYCN amplification, the completeness of surgical resection in our cohort of children older than 1 year of age with a localized unresectable NB tumor without MYCN amplification did not impact EFS and OS,16 In high-risk NBs, the impact of quality resection on OS is still controversial 14,[17][18][19]. Age at diagnosis over 60 months, the preoperative presence of risk factor 33 (tumor surrounding the origin of the celiac axis and/or the superior mesenteric artery) and over five courses of chemotherapy Cox model for the event-free survival and overall survival…”
contrasting
confidence: 64%
“…Achieving GTR has been reported to improve outcomes in some studies of high‐risk neuroblastoma and is influenced by several factors including the site and extent of primary disease, patient comorbidities, and surgical expertise . In the NB97 trial, GTR did not improve OS or local control; however, in the same study, some patients with STR received 36 Gy RT to the tumor bed, whereas none of the GTR patients received RT.…”
Section: Discussionmentioning
confidence: 99%
“…There has been speculation whether the presence of gross disease after surgery can be controlled by a higher dose of radiation (36 Gy) as employed in the NB97 trial. 13 A recent publication reviewed the published locoregional control rates after standard dose radiation (21-24 Gy) versus higher dose radiation (30-36 Gy); in children with STR, local failure was found in 17% to 43% of patients receiving standard and 0% in those receiving higher dose RT. 15 We did not find a difference in locoregional control, progression-free, or OS according to the degree of resection.…”
Section: Acute Toxicity Grade Number Of Patients (%)mentioning
confidence: 99%